Pengaruh Pertumbuhan Perusahaan, Profitabilitas, Kebijakan Dividen dan Struktur Modal Terhadap Nilai Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (Tahun 2020-2024) (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research aims to determine and analyze the influence of company growth, profitability, dividend policy and capital structure on company value. The population in this research is food and beverage plantation sub-sector companies listed on the Indonesia Stock Exchange (2020-2024). The sample for this research was 13 companies. The sampling technique used was purposive sampling. The data collection technique in this research uses documentation techniques in the form of company financial report data. Data were analyzed using descriptive statistics with multiple linear regression analysis by first testing variables from company characteristics. The research results show that company growth, profitability, dividend policy and capital structure have a partial and simultaneous influence on company value.